Thermodynamics and Fluctuations far from Equilibrium - Ross, John (Springer Series in Chemical Physics, 2008)
This book deals with the formulation of the thermodynamics of chemical and other systems far from equilibrium, including connections to fluctuations. It contains applications to non-equilibrium stationary states and approaches to such states, systems with multiple stationary states, stability and equi-stability conditions, reaction diffusion systems, transport properties, and electrochemical systems. The theoretical treatment is complemented by experimental results to substantiate the formulation. Dissipation and efficiency are analyzed in autonomous and externally forced reactions, including several biochemical systems.